Conversion to Islam ceremony interview: starting the interview on the right foot - Tun Nur Afizah Zainal Ariff; Mohd Muzhafar Idrus; Harison Mohd Sidek; Hazleena Baharun (Universiti Sains Islam Malaysia, 2024)
2015 International Conference on Language Education Conference (ILEC’15) Proceeding Palm Seremban, October 7-8, 2015